Insights into brain tumor diagnosis: exploring in situ hybridization techniques - Namiot, E. D.; Zembatov, G. M.; Tregub, P. P. (Frontiers in Neurology, 2024)
Our review examines genetic alterations in various brain tumors, drawing from both standard literature searches and the Online Mendelian Inheritance in Man (OMIM) database (513 records analyzed). One key aspect of our review is our specific focus on mutations that can be identified using hybridization in situ techniques. We recognize the importance of these methods in real-life diagnostics and thus offer a concise overview of the most applicable hybridization techniques for detecting such mutations.To streamline the review and maintain reader engagement, we include figures and tables detailing mutations in each tumor type, emphasizing their clinical implications for treatment responses and prognostic outcomes. Furthermore, we underscore the clinical relevance of these genetic findings by discussing their implications for treatment responses and prognostic outcomes. Ultimately, our review aims to serve as a valuable reference for those conducting similar research or practicing in clinical settings, offering insights into the genetic underpinnings of brain tumors and their therapeutic implications.